Scegliere di partecipare L'impegno dei giovani della provincia di Firenze nelle arene deliberative e nei partiti - Baglioni, Lorenzo Grifone (Strumenti per la didattica e la ricerca, 2011)
The study concentrates on aspects of juvenile participation in the Florentine territory, taking into consideration different forms of political engagement, from that of the traditional party type to that which is expressed through citizen movements and committees, through to the new forms of engaged governance. While the generational data appear to show signs of little emancipation, frequently involving lack of interest, egoism and refuge in a culture of dependence, the young activists - with their direct engagement - contribute to infuse new life into the dynamics of politics. The dimension of active citizenship has important repercussions on the political culture of young people and on their experience of society. Bringing to light the underlying reasons and the specific features is the objective of this work which explores in a qualitative sense one of the salient issues of the previous sample survey Una generazione che cambia. Civismo, solidarietà e nuove incertezze dei giovani della provincia di Firenze (Firenze University Press 2007) edited by the same author.